Metode Extreme Programming Dalam Pengembangan Aplikasi Legalisir Online Berbasis Web Service - Mei Prabowo; Edi Kuswanto (Komputika : Jurnal Sistem Komputer, 2020)
Information System of diploma legalization and academic tanscript services at IAIN Salatiga is still conventional or manual, when alumni want to legalize diplomas, alumni must come directly to campus to legalize diplomas and academic transcripts. This results in a waste of costs and time, especially for alumni who live far from campus. The purpose of this research was to develop an application for legalizing diplomas and academic transcripts online based on web services at IAIN Salatiga. By utilizing web services technology, this system was integrated directly with the Salatiga IIP TIPD Academic Information System database. It was expected that with this application when alumni wanted to make an application for legalization, they did not have to come to campus. The method used in developing this application was extreme programming. In testing, this application was divided based on aspects of Functionality and Usability. From the aspect of functionality, the method used was blackbox testing, the results of testing using blackbox testing was this application was able to run smoothly without any problems. As for the usability aspect using the SUS (System Usability Scale) questionnaire method, in its test, the final SUS value based on respondents' responses showed 79.40 results, and based on system eligibility standards, this application could be interpreted as "Eligible"